The Impact of Family Environment and Learning Independence on Learning Outcomes Through Learning Motivation - Palangda, Listriyanti; Suyono, Desy (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
This study aims to analyze the impact of family environment and learning independence on student learning outcomes through learning motivation at SMKN 1 Tombariri using path analysis. A quantitative approach was used in this study with a survey method to collect data from 66 students through a questionnaire consisting of family environment variables, learning independence, learning motivation, and learning outcomes. Data were analyzed using path analysis techniques to identify direct and indirect relationships between the variables studied. The results showed that the family environment had a significant effect on student learning outcomes through learning motivation. Parental support in the form of attention, the formation of good learning habits, and the provision of learning facilities at home increased student motivation which ultimately had an impact on achieving better learning outcomes. In addition, learning independence also had a significant effect on student learning outcomes through learning motivation. Students who have the ability to learn independently, manage time, and develop learning strategies, show higher motivation, which leads to more optimal learning outcomes. Overall, path analysis shows that the family environment, learning independence, and learning motivation are interrelated and have a direct and indirect effect on student learning outcomes. This finding confirms the importance of synergy between these factors in improving student learning outcomes at SMKN 1 Tombariri.